2021
DOI: 10.2147/opth.s320092
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Surgical Outcomes of Phacoemulsification with Endoscopic Cyclophotocoagulation vs Phacoemulsification with Trabeculectomy and Mitomycin in Cataract and Glaucoma Patients

Abstract: Purpose To evaluate the long-term surgical outcomes of endoscopic cyclophotocoagulation (ECP) after four years follow-up in cataract and glaucoma patients that needed combined phacoemulsification and ECP (phaco-ECP) in comparison to combined phacoemulsification with trabeculectomy (phaco-trabeculectomy) with mitomycin C (MMC). Patients and Methods Retrospective case–control study of 34 patients (34 eyes) with glaucoma who underwent phaco-ECP compared with phaco-trabecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
(39 reference statements)
0
0
0
Order By: Relevance
“…Even in the last visit, the ECP and phaco group maintained favorable results (MD -1.49 mm Hg; 95% CI -2.29 to -0.68; I²=29%; Figure 5 ). This consistent trend aligns with findings in the literature, suggesting a long-term beneficial effect of the combined approach [ 13 , 21 , 25 - 27 ]. The modulating properties of ECP on aqueous humor production may elucidate the enduring benefits of IOP reduction over time.…”
Section: Reviewsupporting
confidence: 92%
“…Even in the last visit, the ECP and phaco group maintained favorable results (MD -1.49 mm Hg; 95% CI -2.29 to -0.68; I²=29%; Figure 5 ). This consistent trend aligns with findings in the literature, suggesting a long-term beneficial effect of the combined approach [ 13 , 21 , 25 - 27 ]. The modulating properties of ECP on aqueous humor production may elucidate the enduring benefits of IOP reduction over time.…”
Section: Reviewsupporting
confidence: 92%
“…Ten of the included studies[ 30 31 33 34 35 36 37 38 39 ] reported the success rate of ECP and non-ECP in treating refractory glaucoma. These values were reported based on the longest follow-up period.…”
Section: Resultsmentioning
confidence: 99%
“…All of the included studies[ 30 31 32 33 34 35 36 37 38 39 ] reported the mean postoperative reduction IOP and with standard deviation after ECP and non-ECP in treating refractory glaucoma. Table 5 is descriptive of the postoperative mean IOP reduction and the mean reduction in IOP lowering medications comparisons between the two groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation